Randomized Trial of the Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of GSK2831781 in Healthy Japanese and White Participants. Issue 11 (11th September 2022) - Liefaard, Lia; Hajduk, Eva; van den Berg, Frans; Panoilia, Eirini; Bouma, Gerben; Lisi, Edoardo; Srinivasan, Naren; Cui, Yi; Gross, Annette S.; Tarzi, Ruth; Marks, Daniel J.B.
Abstract: This study investigated ethnic differences in the safety, tolerability, pharmacokinetics, and pharmacodynamics of GSK2831781, an anti–lymphocyte activation gene 3 (LAG3) monoclonal antibody, in healthy participants, and determined local tolerability and bioavailability following subcutaneous (SC) administration. A double‐blind, randomized study of (A) single intravenous (IV) doses of GSK2831781 450 mg or placebo in Japanese and White participants; and (B) single SC doses of GSK2831781 150 or 450 mg, or placebo in White participants, was conducted. Blood samples for analyses were collected before dosing and over 112 days after dosing. GSK2831781 was well tolerated in Japanese and White participants after both IV and SC doses, with the adverse event profile in Japanese being consistent with other populations. There were no injection site adverse events. There was no evidence of differences in systemic exposure among Japanese and White participants. Systemic exposure did not vary with body weight. SC bioavailability was 76.5%, as estimated using population pharmacokinetic modeling. Full and sustained target engagement and evidence of LAG3 + cell depletion (≈53%–66%) were observed in both populations and after both administration routes. No evidence of reduced circulating regulatory T cells (CD4 + CD25 + CD127 low FoxP3 + ) was observed. Following IV and SC administration, GSK2831781 depleted circulating LAG3 + T cells with no interethnic difference observed. There were no major impacts on circulating regulatory T cells.